Analysis of the Company's Cash Flow Statement Kopinian Café - Aisyah Nurul Aini; Betty Subartini; Muhammad Iqbal Al-Banna Ismail (International Journal of Business, Economics, and Social Development, 2022)
Café is a very popular place for young people today, so many entrepreneurs open up opportunities in this business, but seeing a promising market, entrepreneurs still find it difficult to manage their financial reports. Financial reports are important for a company to know the financial condition of the business being run, and the preparation of non-detailed financial statements will also have a big impact on the company, which causes difficulties in developing a business and including investment capital. With the existence of financial reports on. This writing aims to help the company "Kopinian" Café improve company performance by identifying the company's current financial condition. The cash flow statement method is sourced from the income statement and balance sheet report. This statement of cash flows is prepared with three business activities: cash flows from operating activities, investing activities, and financing activities. Kopinian Café has good management performance, shown by companies that can ideally pay current debts, pay liabilities, and manage inventory turnover.